Transformasi Digital Layanan Gadai Emas: Pengalaman Konsumen dalam Inovasi Layanan Berbasis Aplikasi Tring! by Pegadaian - Sandira, Nur Fadilah Ayu; Sarah, Nulthazam; Iswardhani, Indri; Nasir, Sri Astuti; Oktariani, Andi Rinda (STIM-LPI Makassar, 2026)
This study provides a deeper understanding of how digitalization and service innovation within traditional service institutions are interpreted and experienced by consumers, particularly in the context of gold pawn services through the Tring! by Pegadaian application. The findings indicate that Pegadaian’s digital transformation is not solely oriented toward process efficiency but significantly shapes a service experience that is more convenient, secure, and flexible for users. Perceived ease of use emerges as the most dominant factor in forming a positive consumer experience. A simple interface, clear transaction flow, and the ability to conduct transactions without physical presence enhance perceptions of efficiency and service convenience. These results confirm that the success of digital service innovation largely depends on the extent to which technology aligns with users’ capabilities and needs, rather than merely on system sophistication. Beyond usability, institutional trust plays a central role in the adoption of digital gold pawn services. Pegadaian’s reputation as a state-owned enterprise, the assurance of physical gold availability through a 1:1 system, and data security protections significantly reduce consumers’ psychological risk when engaging in high-value asset-based digital services. This finding suggests that digital transformation in traditional financial services requires a strong foundation of trust to achieve broad acceptance. The study also emphasizes that digitalization does not fully replace conventional services; instead, it fosters a hybrid service model integrating digital and face-to-face channels. This model enables service flexibility while maintaining inclusivity, particularly for consumers with varying levels of digital literacy. Thus, digital innovation functions as a strategic complement that enriches the service ecosystem rather than serving as a complete substitute for physical interaction. Overall, this research contributes to the development of service innovation and consumer experience literature by providing qualitative empirical evidence from a traditional service sector undergoing digital transformation. The findings underscore that the primary value of digitalization lies in consumers’ subjective experiences and in the organization’s ability to continuously align technology, trust, and integrated service channels.